GENERAL CULTURE IN EDUCATORS OF PRESCHOOL EDUCATION ORGANIZATION DEVELOPMENT OF COMPETENCE - Olimova, Dilrabo (Educational Research in Universal Sciences, 2022)
This article provides information about the competence of educators of the future preschool educational organization, the formation of the competence of social development of students, and the requirements for the pedagogical activity of educator-pedagogues.